Gambaran Cara Orang Tua dalam Membentuk Kebiasan Belajar Menurut Anak di Jorong Alamanda Kenagarian Kinali Pasaman Barat - Ringga Amla; Ismaniar Ismaniar; Vevi Sunarti (Universitas Negeri Padang, 2018)
This research is motivated by the number of teenagers who get good learning outcomes at SLTP Kanagarian Kinali level, Kinali District, West Pasaman District. The purpose of this study is to describe the parent's way of forming the child's learning habits in terms of the following aspects: 1) arranging the learning schedule together with the child, 2) accompanying and assisting the child in learning, 3) giving praise to the child and 4) assisting the child in eliminating anxiety and saturation in learning. This research uses quantitative descriptive method. The population in this study all teenagers amounted to 109 people. Samples taken 25% using stratified rondom sampling technique, jad i amounted to 27 people. Data collection techniques used observation and questionnaires. Technique of data analysis using technique percentage. The result of this research show that parent in forming child's learning habit is included into good category. Based on the results of research, it is suggested to parents to be able to further improve again how to form a child's learning habits.